Differential Diagnosis of Irritant Versus Allergic Contact Dermatitis Based on Noninvasive Methods - Panagiota Gkagkari; Anna Tagka; Alexandros Stratigos; Vangelis Karalis; Aikaterini Kyritsi; Andreas Vitsos; Michail Christou Rallis (Mattioli1885, 2024)
Introduction: Irritant contact dermatitis (ICD) is characterized by direct injury to the epidermal cells, activating the innate immune response. Allergic contact dermatitis (ACD), in contrast, is delineated by a delayed hypersensitivity reaction of type IV. Despite the distinct etiopathogenic mechanisms underpinning each condition, the differentiation between them presents a significant diagnostic challenge. Objective: This study aims to determine whether a combination of clinical evaluation and noninvasive measurements-encompassing oxidative stress, erythema, hydration, melanin content, transepidermal water loss (TEWL), hemoglobin concentration, and skin texture and volume-can distinguish ICD from ACD. Methods: Two cohorts, each comprising 21 patients, were evaluated: one diagnosed with ICD and the other with ACD. All participants underwent biophysical and clinical assessments, along with Antera® 3D evaluations. Tape strips were utilized for skin sampling, and oxidative stress levels were measured via fluorescence assessments. Results: ICD prompts an almost immediate inflammatory reaction (peaking at 24 hours), whereas ACD incites a delayed response (72 hours). Noninvasive evaluated parameters as hemoglobin concentration, skin texture and volume, melanin content, erythema, and TEWL showed significant differences between the ICD and ACD cohorts (p < 0.05).  The allergens amcinonide, nickel sulphate, cobalt chloride, budesonide, PPD, and thiuram mix were found to induce elevated levels of oxidative stress. Conclusions: The evaluation of patients with noninvasive parameters, including transepidermal water loss (TEWL), hemoglobin concentration, and skin texture and volume, could markedly aid in distinguishing irritant contact dermatitis  from allergic contact dermatitis (ACD). Nevertheless, the study is constrained by a limited sample size.